Bilqis ANALISIS EFEKTIVITAS, EFISIENSI, DAN CAPAIAN KINERJA PENYERAPAN ANGGARAN PERIODE 2019 – 2021 PEMERINTAH KOTA BALIKPAPAN: Bilqis Nabilah - Bilqis Nabilah; Nadi Hernadi Moorcy (MEDIA RISET EKONOMI [MR.EKO], 2023)
This study aims to determine out how well the financial performance of the Balikpapan city government for the period 2019 - 2021 is measured based on effectiveness ratios, efficiency ratios, achievement of budget absorption performance. The type of research used in this study is quantitative descriptive. The data processed is a report on the realization of the Balikpapan city government budget from 2019 to 2021. The data collection techniques used in this study is documents, observation (direct observation), and literature study. The data analysis technique used in this study is descriptive statistics. The results identifie that the level of effectiveness is with a different percentage but within the same effectiveness criteria, the 2019 period was 86% (effective enough), the 2020 period was 90% (effective enough), and the 2021 period was 84% (effective enough). Where as at the level of efficiency with varying results, the 2019 period at 95% (less efficient), the 2020 period at 87% (quite efficient), and the 2021 period at 90% (quite efficient). The budget absorption performance achievements were well absorbed, but there were still some expenditures that did not reach the target due to existing policies and their realization according to the needs of the current period.